Classic Football Debates Settled Once and for All (Vol.I) - Baker, Danny, 1957- and Kelly, Danny, 1957- (London Ebury Press, 2009)
A work on football that answers such questions as: which clubs has the handsomest fans; who is the greatest player of all time, Pele, Maradona, Puskas, Rougvie; have foreign players helped or hindered the English game; and, which was the most tip top ever World Cup
Include Color Illustration
Keywords: Soccer